Performance evaluation of developed mixed cement containing asphalt waste dust and class-C fly ash in sulfate salt solution test - Sertsoongnern, Pimchanok; Ayawanna, Jiratchaya; Chaiyaput, Salisa (My University, 2024)
The performance of newly developed cement mixes comprising asphalt waste dust and fly ash for construction in areas with high sulfate salt content was evaluated in this study. In comparison to 100% Ordinary Portland cement Type 1 (OPC), mixes of 50 wt% OPC with 20 wt% asphalt waste dust and 30 wt% fly ash, as well as 50 wt% OPC with 50 wt% fly ash, were tested over a 30- and 90-day comparative study in magnesium sulfate solution, respectively. The compressive strength, weight change, and expansion of mixed cement samples are investigated through chemical, phase, and microstructural studies. The replacement of 50% OPC with fly ash and asphalt waste dust prevented the samples from expanding and cracking in the sulfate salt solution during the 90-day test period. By using fly ash at less than 50 wt% in combination with asphalt waste dust, a dense microstructure was obtained, inhibiting the formation of the harmful magnesium silicate hydrate phase and the degradation of strength in the mixed cement samples.
Keywords: Cement mixes; Fly ash; Magnesium sulfate; Strength; Waste dust